2015
DOI: 10.1186/s41065-015-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

The Trp719Arg polymorphism of the KIF6 gene and coronary heart disease risk: systematic review and meta-analysis

Abstract: BackgroundGenetic factors play an important role in the pathogenesis of coronary heart disease (CHD). Kinesin-like protein 6 (KIF6) is a new candidate gene for CHD, since it has been identified as a potential risk factor. The aim of this study was to perform a systematic review and meta-analysis of previously published association studies between the Trp719Arg polymorphism of KIF6 and the development of CHD.MethodsStudies and abstracts investigating the relationship between the Trp719Arg polymorphism of KIF6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…We found that there was a statistically significant correlation between being a sufferer of MACE and being a carrier of c.2155T> C variant of KIF6 when taking into consideration all patients prior to treatment with statins (p = 0.049). This outcome is consistent with the current literature [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…We found that there was a statistically significant correlation between being a sufferer of MACE and being a carrier of c.2155T> C variant of KIF6 when taking into consideration all patients prior to treatment with statins (p = 0.049). This outcome is consistent with the current literature [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…The KIF6 c.2155T>C variant was reported to increase the risk of CHD in statin-free patients [47]. However, it was shown to reduce coronary events while on statin therapy [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the present era, the world is focusing on studying the role of genetic variants and their role in the pathogenesis of CAD (37). KIF6 is a member of a family of molecular motors involved in the intracellular transport of protein complexes, membrane organelles, and messenger ribonucleic acid (mRNA) along microtubules in an ATP-dependent process (15).…”
Section: Discussionmentioning
confidence: 99%